Analisis Hukum Islam dan Hukum Positif Terhadap Akad Jual Beli Makanan Dengan Tambahan Pajak - Nutqi, Prisma Winda; Khasanah, Karimatul (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2022)
The Sari Raos Restaurant in the Pekalongan City branch is one of the taxpayer restaurants that is the focus of the author's research, because the tax burden on buyers is not notified at the beginning of the sale and purchase agreement. The purpose of this study is to find out the provisions of positive law and Islamic law on food buying and selling contracts with additional taxes and to analyze food buying and selling contracts with additional taxes at Sari Raos Restaurant Pekalongan City branch. This research includes empirical legal research that uses primary data and secondary data. The data collection techniques were carried out by observation, interviews and documentation. Based on the results of the study, the practice of buying and selling food with additional taxes at the Sari Raos Restaurant in the Pekalongan City branch if viewed from a positive law, the imposition of food taxes is a necessity that has been regulated in Law Number 28 of 2007 concerning General Provisions and Tax Procedures (KUP). ) and strengthened by Regional Regulation Number 2 of 2013 concerning Amendments to the Regional Regulation of Pekalongan City Number 4 of 2011 concerning Restaurant Tax. However, in the regulations there are no specific rules regarding the procedure for collecting it, so in practice in the field, different methods are often found. As for the method used by the Sari Raos Restaurant in the Pekalongan City branch, when viewed from the perspective of positive law in Indonesia, there are no contradictory things. However, if you use the perspective of Islamic law, the existence of a tax imposition that is not notified is possible to contain an element of gharar because the object requirements in the form of a price are not clarified at the beginning of the contract.